2021
DOI: 10.1038/s41598-021-98876-y
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary analysis of Italian Alpine wildflower honey reveals criticalities, diversity and value

Abstract: Wildflower honeys produced in mountain grasslands are an expression of the biodiversity of these fragile habitats. Despite its importance, the botanical origin of honey is often defined without performing formal analysis. The aim of the study was to characterize six wildflower mountain honeys produced in the Italian Alps with different analytic techniques (SPME–GC–MS, HPLC-Orbitrap, cicatrizing and antioxidant activity) alongside melissopalynological analysis and botanical definition of the production area. Ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 80 publications
0
19
0
Order By: Relevance
“…Resonances of minor compounds also play a certain role such as quinoline alkaloids and kynurenic acid for chestnut honey ( Truchado et al, 2009 ). Kynurenic acid was found in small concentrations in Alpine honey from Italy ( Leoni et al, 2021 ). In Moroccan jujube Ziziphus lotus honey kynurenic acid contents were 17.7 mg/kg by HPLC-DAD-ESI-MS and 6.6 mg/kg by GC-EI-MS ( Khallouki et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Resonances of minor compounds also play a certain role such as quinoline alkaloids and kynurenic acid for chestnut honey ( Truchado et al, 2009 ). Kynurenic acid was found in small concentrations in Alpine honey from Italy ( Leoni et al, 2021 ). In Moroccan jujube Ziziphus lotus honey kynurenic acid contents were 17.7 mg/kg by HPLC-DAD-ESI-MS and 6.6 mg/kg by GC-EI-MS ( Khallouki et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the development of plant communities such as the Rubetum idaei after the disturbance event, where important foraging resources for solitary and domestic bees as Rubus idaeus are present [ 79 ], could favor the communities of pollinators in higher mountain habitats, providing an environment richer in foraging resources compared with the previous Calamagrostio arundinaceae-Piceetum spruce forests. Additionally, the clearings in the canopy create more nesting sites for some solitary bees such as bumblebees, too [ 80 , 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…Very few studies on nicotinaldehyde are reported in the scientific literature. Nicotinaldehyde is a natural compound found in plants and bacteria, which can also be contained in foods of plant origin such as honey [17]. However, little is known about the role of nicotinaldehyde in the NAD metabolism in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Nicotinaldehyde is a natural compound found in plants and bacteria, and it is used as an intermediate for molecule synthesis in the pharmaceutical and agronomical industries. It can also be contained in foods of plant origin such as honey [17]. To date, only a few studies have investigated the role of nicotinaldehyde in NAD metabolism in humans.…”
Section: Introductionmentioning
confidence: 99%